13 - African Fellowships for Research in Indegenous and Alternative Knowledge (AFRIAK): CONFERENCE CALL FOR PAPERS - CODESRIA (CODESRIA Bulletin, 2025)
The Council for the Development of Social Science Research in Africa (CODESRIA) is pleased to announce a call for proposals for a new research and fellowship programme, the African Fellowships for Research in Indigenous and Alternative Knowledges (AFRIAK). This programme is o!ered with the support of the Mastercard Foundation as part of the Foundation’s commitment to advance education and skills for young people in Africa, and in recognition of the contribution of the late Ghanaian intellectual, Dr Sulley Gariba, in advocating for the place of African knowledge in Research and Evaluation. This programme seeks to implement an innovative approach to training a new generation of young people to design research projects and produce knowledge as a partnership between academic mentors on the one hand and bearers of Indigenous knowledge on the other. This approach will privilege local, Indigenous and endogenous knowledge as forms of knowledge or knowledge systems that are deeply embedded in communities and closely tied to their lived experiences. Although these forms of knowledge may be geographically proximate to the young people in Africa, they remain inaccessible to them partly because of the dominance of Western formats of learning in our school and university curriculum and partly owing to the gerontocratic nature of our communities, where such knowledge is preserved for a few, predominantly male, knowledge-bearers. The AFRIAK approach is innovative because it re- directs us to use what we have in our communities and invites us to appreciate the many ways in which what we have in our communities is used, preserved and disseminated.